РАЗВИТИЕ ЭКСПОРТА ТРАНСПОРТНО-ЛОГИСТИЧЕСКИХ УСЛУГ КАЗАХСТАНА КАК ОДНОГО ИЗ ПЕРСПЕКТИВНЫХ НАПРАВЛЕНИЙ ВЫСОКОТЕХНОЛОГИЧНОГО ЭКСПОРТА (Экономика: стратегия и практика, 2019)
The purpose of this research is to analyze the export potential of transport and logistics services, identify factors affecting exports and justify its development directions for Kazakhstan in order to increase the share of high-tech exports.In this study have used the scientific research methods: systematic approach, logical analysis, comparisons, alogi es,abstractions,identifications,typologies,generalizationand concretization. Based on the analysis, it was revealed that transport services are dominated in the structure of service exports, with freight transport taking the largest share in the structure of exporting transport services, among which railway transportation is leading. Further,ithavestudiedthe problems of the development of freight traffic in the context of various types of transport, as well as in the context of countries-importers of transport services provided by transport companies of the Republic of Kazakhstan. It was revealed that in the conditions of increasing competition for transit, as well as against the background of domestic political and economic competition in the region, for Kazakhstan there are a number of obstacles to the transit of goods. The organizational and technical factors that complicate the export of transport and logistics services in Kazakhstan are highlighted. Ithavegiventhe directions for the development of export of transport and logistics services, such as the creation of an efficient infrastructure, the improvement of transport and logistics operations on any type of transport, taking into account the provision of a wide range of services, the offer of competitive tariffs, and the further improvement of corridors for transit cargo flows.